2015
DOI: 10.1021/acs.langmuir.5b02678
|View full text |Cite
|
Sign up to set email alerts
|

Probing Anisotropic Surface Properties of Molybdenite by Direct Force Measurements

Abstract: Probing anisotropic surface properties of layer-type mineral is fundamentally important in understanding its surface charge and wettability for a variety of applications. In this study, the surface properties of the face and the edge surfaces of natural molybdenite (MoS2) were investigated by direct surface force measurements using atomic force microscope (AFM). The interaction forces between the AFM tip (Si3N4) and face or edge surface of molybdenite were measured in 10 mM NaCl solutions at various pHs. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 56 publications
5
89
1
Order By: Relevance
“…On the topographic AFM image of freshly polished edge plane shown in Figure 4A, the dark regions were polishing defects that could not be totally avoided, while the bright regions were the aggregates possibly arising from the edge crystal structure. The rms roughness of the polished edge plane was measured to be 1.61 nm, which was smoother than the MoS 2 edge plane obtained by the ultramicrotome cutting technique (1.6–3.3 nm) reported previously (Lu et al, 2015, 2016). Since the edge plane was not as molecularly smooth as the basal plane, the polishing defects and aggregates pre-existed on the edge plane might affect the determination of adsorbed polymer.…”
Section: Resultscontrasting
confidence: 58%
See 3 more Smart Citations
“…On the topographic AFM image of freshly polished edge plane shown in Figure 4A, the dark regions were polishing defects that could not be totally avoided, while the bright regions were the aggregates possibly arising from the edge crystal structure. The rms roughness of the polished edge plane was measured to be 1.61 nm, which was smoother than the MoS 2 edge plane obtained by the ultramicrotome cutting technique (1.6–3.3 nm) reported previously (Lu et al, 2015, 2016). Since the edge plane was not as molecularly smooth as the basal plane, the polishing defects and aggregates pre-existed on the edge plane might affect the determination of adsorbed polymer.…”
Section: Resultscontrasting
confidence: 58%
“…In our previous study, the adsorption of guar gum on MoS 2 basal plane was found to lead to the formation of interconnected polymer network at 5 ppm and a fully covered polymer film at 10 ppm (Xie et al, 2017d). It is evident that the adsorption of CMC is more difficult than guar gum most likely due to the negatively charged carboxyl groups of CMC that could induce stronger electrostatic repulsion with the negatively charged MoS 2 basal plane (surface potential at pH 9: −55 mV in 1 mM NaCl and −44 mV in 10 mM NaCl) (Lu et al, 2015; Xie et al, 2017d). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These attractive forces may be due to the presence of nano bubbles present at such hydrophobic surfaces. As suggested in the literature, when two hydrophobic surfaces are brought close to each other, capillary bridging between these nano bubbles takes place leading to attraction which can be considered to be an explanation for hydrophobic interactions [34][35][36][37][38][39][40][41]. One more observation that can be made from Fig.…”
Section: Afm Surface Force Measurementsmentioning
confidence: 61%